ANALISIS AKTIVITAS BELAJAR SISWA KELAS IV PADA MATA PELAJARAN BAHASA INDONESIA DI UPTD SDN TANJUNG JATI 2 - Makkiyah, Nurul; Dya Qurotul A’yun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning activities are an essential factor in determining students' learning success because they reflect students' participation throughout the learning process. This study aimed to describe the learning activities of fourth-grade students in Indonesian language learning at SDN Tanjung Jati 2. The research employed a qualitative approach with a descriptive design. The participants consisted of one fourth-grade teacher and four students selected based on different levels of learning activity, namely very active, active, passive, and very passive. Data were collected through classroom observations, interviews, and documentation. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings revealed that the dominant learning activities were visual, oral, and listening activities, as reflected in students' attention to learning materials and media, participation in discussions, expression of opinions, and attentiveness to teachers' explanations and peer discussions. Other types of learning activities appeared less frequently because they depended on the learning objectives, instructional materials, and teaching strategies implemented. The study concludes that students' learning activities have not yet developed evenly across all indicators, highlighting the need for more varied instructional strategies to promote comprehensive student engagement.